The impacts of a community orchestra in a rural setting: An insight into Borderland Community Orchestra. Issue 3 (1st December 2015) - Darby, Shannon
This article investigates the cultural impacts of a community orchestra in a rural setting through the examination of 'Borderland Community Orchestra', a crossborder ensemble operating in northern Ontario, Canada and northern Minnesota, United States. In May 2013, two surveys were conducted to understand how members of the orchestra and other community residents perceived the ensemble's role in the rural arts culture of the area. The themes that emerged include the enrichment of local arts, importance of word-of-mouth communication and sense of community. Throughout the article, survey findings are reinforced by modern literature to demonstrate the necessity of community ensembles in the development of rural arts and the challenges of achieving sustainability. Survey responses are collected into three recommendations, which will assist Borderland Community Orchestra and other ensembles to more effectively connect with their communities: (1) Better marketing and increased awareness; (2) Perform more concerts; (3) Youth outreach and involvement. The conclusions illustrate the power of community musicmaking and deepen the understanding of community orchestras operating in rural areas around the world.